FORMATION OF PERFORMING SKILLS OF STUDENTS THROUGH SAMPLES OFMAKOMS ART - Acting Professor Kodirov.D.K. (Western European Studies, 2024)
This article provides methodological guidance and practical tasks on the formation of performing skills of students through the samples of status art to our young people on their ability to read, practice, perform and perceive our musical heritage created in the past. The processes of teaching Segox singing are presented
Keywords: Ystoz-shogird; Allas; laments; military conscription